Balancing between environmental impact and vibroacoustic performance for lightweight buildings - Carlsson,Philip (TVSM-5000, 2021)
Multi-storey buildings constructed in timber have become more common in recent years. A reason for this lies in the growing interest for sustainable building, where timber is seen as a particularly interesting alternative. As efforts have been made to improve the heat insulation in buildings, the energy consumption from manufacturing materials and from constructing buildings, referred to as embodied energy, accounts for an increasing proportion of the total energy consumption during the lifetime. Timber buildings offer an alternative for reducing the embodied energy as compared to traditional concrete buildings. However, timber buildings are more sensitive to low-frequency noise and vibrations, and studies have shown that exposure to high levels of noise and vibration increases the risk of anxiety, sleep disturbance and hearing loss. Consequently, this implies a balancing between embodied energy and noise and vibrations. This dissertation investigates such balancing when comparing timber buildings to traditional concrete buildings. In this dissertation, different methods for calculating the vibroacoustic performance as a single scalar value are conducted in order to directly compare the vibroacoustic performance with the environmental impact of different choices of material. An LCA is conducted for the embodied energy and global warming potential of a CLT floor, a concrete-CLT composite floor, and a prestressed concrete floor using data provided by manufacturers and existing databases. Finite element models of the different floors are created, and the vibration levels are investigated for a unit load and footstep pulse. A parameter study is performed where the thickness of the CLT floor is varied. The different floors are compared in terms of vibroacoustic performance and LCA. Moreover, 2D finite element model of a ground with a building placed on top is created where the vibration levels are investigated for a unit load placed 20 m from the building to analyse the vibroacoustic performance due to an external load. The buildings investigated for external loading are a lightweight building with CLT floors or CLT-concrete composite floors, and a concrete building with prestressed concrete floors. A parameter study is performed for varying thicknesses of the CLT floors, and the buildings are compared for the vibroacoustic performance and LCA of the load-bearing structure. The results show that the CLT floor and the composite floor has a higher vibration in relation to the concrete floor when exposed to an internal load. However, a seven-layered CLT floor with 50 mm ply thickness or a composite floor provides a relatively good vibroacoustic performance in relation to a concrete floor. The good vibroacoustic performance in the two aforementioned floors is more evident when evaluating the vibrations based on thresholds for human disturbance of vibrations. The CLT floors and the composite floor have a low global warming potential and a low non-renewable energy consumption compared to the concrete floor, while the total energy consumption is similar or higher than concrete due to energy demanding process of CLT manufacturing. A general trend is observed where an increase in the thickness of a CLT floor improves the vibroacoustic performance. However, in some cases increasing the thickness resulted in a worse performance and the response proved to be sensitive to the walking frequency applied. The results suggest that when only considering absolute values, rather than thresholds, a good balance may be difficult to achieve as a very thick CLT floor would be required to achieve a similar vibroacoustic performance when exposed to an internal load. The lightweight buildings have a lower vibration magnitude in relation to the concrete building when exposed to an external load, while having a lower global warming potential and use of non-renewable energy, but a higher total energy consumption. The results show that the response of the buildings is sensitive to the eigenfrequencies matching to the frequency content of the propagating ground waves making the optimal material selection very much specific to each case.